Жидкофазное фторирование органических соединений фтором; Фторидные материалы и технологии - Пашкевич Д. С. Дмитрий Станиславович; Камбур П. С. Павел Сергеевич; Белов Н. А. Николай Александрович; Алентьев А. Ю. Александр Юрьевич; Мухортов Д. А. Дмитрий Анатольевич; Блинов И. А. Илья Андреевич; Ворошилов Ф. А. Федор Анатольевич; Капустин В. В. Валентин Валерьевич (2024, 2024)
Заглавие с экрана